DEVELOPMENT OF ETHNOSAINS-BASED LEARNING MODULE THEME ACID AND BASE FOR SENIOR HIGH SCHOOL CLASS XI - Fiesta Iqlima Maytrea; Irah Namirah; Solfarina Solfarina (Universitas Negeri Surabaya, 2020)
This research-based on decreasing cultural identity because of the process of globalization and limited modules used in learning that integrated with culture. This research aims to determine the validity of ethnoscience based learning modules with the theme of acids and bases and to find out the response of class XI students to the modules used. The research method is Research and Development (R&D) which includes several stages: problem identification, data collection, design module, design validation, design revisions, small-scale trials, and final module. The results showed that the modules developed according to BSNP valid with Aiken calculations for aspects of content and media were 0.99 and 0.97. As for the responses of students in the high, medium and low groups, and the percentage 92%, 93%, and 92% which are included in the category very good. The developed module has proven valid to use in learning.